(3UMI GdYjfs - (3CHh GdMSf SYjO Hf gHg Gddg Hf GdMSjf GdajdSha,J (B495 (3g` s
(3ChdgG (B:s
(3ehGO UMI GdYjf GKfGf(B: (3CMOgeG , eYQaI GdCTjGA GdJi jchf ajgG GdUMI hgiGdYjf hGdKGfi , eYQaI GdCTjGA GdJi jchf HgG JJe GdUMI s
(3BNQgG (B:s
(3fWQhf eNaa eMdd jbdY HjGV GdYjf MQa GdgGA (B: (3gfO HGHGQOI QWHI ajgG bHV jSjQ jfaY ChQGe GdYjf GdMGOI VeGOoG s
(3LGA ai HWGbI GdeagQS (B: (3cJGH aj GdWH dCHj GdMSf SYjO Hf gHI Gddg GdajdSha ceG LGA ai Chd GdfSNIHNW MOjK (B: (3cJGH JPcQI GdcMGdjf hde fLO eGjDjO gPG Ch PGcs
(3hjdjg fbhds
(3hahGFO WjHI HNWhW oeNJdaIs
(3de ojYde eDdag s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdWHs